2020
DOI: 10.1177/0032258x20977024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal characteristics and weather conditions on speeding sanction rates in automatic traffic enforcement

Abstract: Speeding is dangerous and contributes significantly to traffic safety. Despite that, speeding is not perceived as serious crime, and has been a relatively neglected topic in criminology. The purpose of this study is to analyse the effects of different temporal characteristics and weather conditions on speeding sanction rates in automatic traffic enforcement. The analysis focuses on two major highways in Finland. Generalized additive models are used to analyse factors influencing the sanction rates. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
1
0
0
Order By: Relevance
“…More serious summer traffic offenses may be associated with a high temperature. A prior study found that drivers are more likely to drive at higher speeds in high-temperature environments [39]. In addition, further studies have found that deaths are related to traffic accidents mostly most frequently in summer [40], and this consequence confirms the discussion above.…”
Section: Individual Factorssupporting
confidence: 72%
“…More serious summer traffic offenses may be associated with a high temperature. A prior study found that drivers are more likely to drive at higher speeds in high-temperature environments [39]. In addition, further studies have found that deaths are related to traffic accidents mostly most frequently in summer [40], and this consequence confirms the discussion above.…”
Section: Individual Factorssupporting
confidence: 72%